TOWARDS AN IT-ENABLED FRAMEWORK FOR REMOTE WORK IMPLEMENTATION: MENUJU KERANGKA KERJA TEKNOLOGI INFORMASI UNTUK KERJA JARAK JAUH - Alfa Yohannis; Glenny Chudra; Julian Yang (LPPM Universitas Abdurrab, 2026)
This study identifies the essential components of an IT-enabled socio-technical framework to support effective remote work implementation. It draws on employees’ experiences and perceptions during the shift from office-based to remote arrangements, examining four dimensions: perceived advantages, perceived disadvantages, technological requirements, and ethical considerations in distributed work settings. Data were collected through an online questionnaire across multiple sectors, yielding 97 valid responses, predominantly from knowledge-intensive and digitally enabled organisational contexts. Qualitative thematic analysis revealed flexibility, time efficiency, and reduced commuting costs as key benefits, while communication difficulties, work–life imbalance, and technical limitations were cited as major challenges. Respondents also emphasised the importance of integrated digital tools, reliable infrastructure, and ethical guidelines related to privacy, trust, and fairness. These findings informed the proposal of six interrelated components forming a preliminary IT-enabled framework intended to support sustainable remote work practices. The anonymised dataset is openly available to encourage further research and contextual validation.